(3OQhH CfOdSjI (B:s (3QMdI aj CfOdS GdeGVj hGdMGVQ (B/s - (3GdMeGOj, YHO GdhgGH eMeO,s 1979- ((3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ cJGH ddfTQ,s, 2014)
(3cJGH QGFY LOG JedF UaMGJg JaGUjd CfOdSjI LejdI hjTYQc HCf GdCfOdS SJHbi fGHVI HGdMjGI ajfG OheG heG RGdJ GdCfOdS aj hLOGf cd eSde hYQHj cJGH UZjQ GdMLe LeY cGJHg Hjf OaJjg JGQjNG ddCfOdS fSLg HMQha GdeTGYQ hGdcJGH Naja hLejd aj COH GdQMdGJ hGdcGJH GNJGQ GSHGfjG YTGf jPcQfG HGdCfOdS GdLejd GdcJGH edjGf UhQ hGTjGA cKjQI Yf JGQjN GdCfOdS(B.s
(3GdeMJhjGJ (B: (3TcQG dgDdGA hgDdGA(B-(3GdebOeI (B: (3deGPG(B-(3eONd (B: (3YfOeG CHUQJ GdOQH(B-(3GdOQH GdChd (B: (3bQWHI (B.. (3bHdI GdJGQjN(B-(3GdOQH GdKGfj (B: (3GdRgQGA (B.. (3RgQI GdcJH(B-(3GdOQH GdKGdK (B: (3ETHjdjI (B.. (3eedcI GdTYQ(B-(3GdOQH GdCNjQ (B: (3ZQfGWI(B.. (3BjI GdYQHj GdCNjQI(B-(3eNQL (B: (3bHd GdhOGY, cdeI(B.s
(3GdZdGa (B: Kuttab Team (3; JUhjQ (B: (3YHO GdhgGH GdMeGOj(B.s
Keywords: (3GdCfOdSs -- (3hUa hQMdGJs